PRODUCT QUALITY CONTROL AS A KEY FACTOR FOR THE SUCCESS OF THE RESTAURANT BUSINESS (Development Service Industry Management, 2025)
The article examines product quality control as a key factor in the success of the restaurant business in conditions of high competition. It is substantiated that an effective quality control system directly affects the safety of food products, the stability of the taste characteristics of dishes and the level of consumer trust. The main stages of product quality formation are considered - from the selection and supply of raw materials to the preparation, storage and serving of finished dishes. The role of proper procurement planning and compliance with optimal product storage conditions is analyzed. Special attention is paid to temperature regimes, labeling, the FIFO principle and the prevention of cross-contamination. The value of technological charts as a tool for standardizing production processes and ensuring stable quality of dishes is determined. The impact of compliance with technological cooking regimes on the taste properties and safety of products is characterized. The essence of organoleptic evaluation as an effective method of quality control of finished dishes is revealed. The main methods of sensory analysis are described, in particular, tasting, visual assessment and aroma analysis. Attention is focused on the importance of systematic use of the results of organoleptic evaluation in improving the menu. The role of sanitary and hygienic standards in ensuring product quality and safety is analyzed. The importance of personal hygiene of personnel and cleanliness of production premises is determined. It is shown that compliance with hygiene requirements is a component of the professional culture of a restaurant establishment. The importance of feedback from guests as a tool for quality control and improvement is investigated. The main methods of collecting and analyzing consumer feedback are considered. The impact of working with feedback on increasing the level of service and customer loyalty is substantiated. It is proven that a systematic approach to quality control contributes to the optimization of production processes and the reduction of financial losses. The relationship between product quality, the image of the establishment and its competitiveness is shown. It is generalized that quality control is a strategic tool for managing the restaurant business.
Keywords: quality control; restaurant business; technological maps; organoleptic assessment; product safety; quality management